2022
DOI: 10.3390/jcdd9100346
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Uric Acid and Hypertension in a Large Cross-Section Study in a Chinese Population

Abstract: Background: The association of serum uric acid (SUA) with hypertension has been well established in Caucasian populations. However, its association with hypertension in Chinese remained to be clarified. Methods: Consecutive patients, homogeneous in Chinese Han ethnicity, aged ≥18 years, abstracted from the database, admitted from 1 January 2010 to 31 December 2013, were included for potential analysis. The patients were grouped according to the presence or absence of hypertension. Unconditional logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…[ 45 ] And a cross-sectional study based on a Chinese population also showed that UA was dose-response associated with hypertension in the Chinese hospitalized population. [ 46 ] Our results support the findings of prior studies showing UA content is positively correlated with the risk of hypertension. There are a number of mechanisms underlying the beneficial association between UA and hypertension, including decreased endothelial nitric oxide, activation of the renin-angiotensin system, and renal microvascular disease brought on by smooth muscle cell proliferation, inflammation, and local renin-angiotensin system activation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[ 45 ] And a cross-sectional study based on a Chinese population also showed that UA was dose-response associated with hypertension in the Chinese hospitalized population. [ 46 ] Our results support the findings of prior studies showing UA content is positively correlated with the risk of hypertension. There are a number of mechanisms underlying the beneficial association between UA and hypertension, including decreased endothelial nitric oxide, activation of the renin-angiotensin system, and renal microvascular disease brought on by smooth muscle cell proliferation, inflammation, and local renin-angiotensin system activation.…”
Section: Discussionsupporting
confidence: 92%
“…[45] And a cross-sectional study based on a Chinese population also showed that UA was dose-response associated with hypertension in the Chinese hospitalized population. [46] Figure 2. Nomogram for the risk of hypertension for patients with periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that individuals with very high (99 th percentile) SU cross-ancestry PRS had 7.00-, 1.37-, and 1.34-fold higher risks of gout, heart failure, and hypertension, respectively, than those with low (0–19 th percentile) SU cross-ancestry PRS. The association between SU and hypertension, shown in previous observational studies, was also confirmed using PRS in the East Asian population 54 . These results suggest that PRS can help identify individuals with a high genetic predisposition to specific diseases associated with SU, though the predictive ability should be improved.…”
Section: Discussionsupporting
confidence: 76%
“…Serum UA was linked to hypertension in a dose-response manner in a Chinese hospitalized population in a sizable cross-sectional investigation based on a Chinese population. [ 29 ] Another Chinese cross-sectional study that included an analysis of prehypertension found that higher serum UA levels were positively associated with prehypertension and hypertension in Chinese adults. [ 30 ] Our research revealed that the association between UA and hypertension was influenced by race.…”
Section: Discussionmentioning
confidence: 99%